ATIVIDADES ANGIOGÊNICA, ANTIINFLAMATÓRIA, CICATRIZANTE E ANTIBACTERIANA DO EXTRATO ETANÓLICO E FRAÇÕES DAS FLORES DA Calendula offIcinalis L. CULTIVADAS NO BRASIL - PARENTE, Leila Maria Leal (2008)
The Calendula officinalis L. is an annual herb, originating in the Mediterranean region, belonging to the Asteraceae family and well known as calendula. Displays orange or yellow flowers, which are attributed medicinal properties, with emphasis on healing activity. In this study, the ethanolic extract of flowers of C. officinalis grown in Brazil was prepared by soaking the cold and fractionated to obtain fractions of dichloromethane and hexane. The angiogenesis activity of the extract and fractions was evaluated using the model of membrane corioalantóide in embryonated chicken eggs. But the healing effect of the extract was evaluated by the model of skin wounds in rats, with assessment of macroscopic and microscopic characteristics. In this model, the ethanol extract of angiogenesis activity in the dermis of rats was also evaluated by immunohistochemistry, and measured the intensity of expression of vascular endothelial growth factor (VEGF). The in vitro antibacterial activity of extract and fractions was evaluated by determining the minimum inhibitory concentration (MIC) using the dilution plate. The ethanol extract and the fractions of calendula showed marked angiogenesis activity, demonstrated in both experimental models used. This activity was not related to the observed increase in intensity of expression of VEGF, which may be related to other pro-angiogenic factors. In the model of skin wounds in rats the ethanolic extract showed anti-inflammatory activity, demonstrated by the decrease in serous exudation of hyperemia, the deposition of fibrin and epidermal hyperplasia, besides the presence of more thin crusts and soaked in the control group. There was an increase in the amount of collagen in granulation tissue and antibacterial activity was observed, mainly on gram-positive bacteria. Still, the C. officinalis served as positive about the process of vascular neoformation and activity in healing skin wounds in rats, and also presented antibacterial activity in vitro. Thus, it is the healing effect attributed to this species